Australia's Vietnam War - Doyle, Jeff, 1952-; Grey, Jeffrey; Pierce, Peter, 1950- (Texas A & M University military history series, 2002)
"Australia's Vietnam War shows the consequences of war in Australia. Through an evaluation of the literature arising from that experience, the manner in which their country memorialized its fallen veterans, and also other expressions of the war's influences, this book offers important insights into the healing process nations face following such conflicts."--Jacket